Metabolic phenotypes in a Lyz2Cre recombinase mouse model - Rahman, S. M. Niazur; Yung, Justin Hou Ming; Volchuk, Allen; Goldenberg, Neil M.; Giacca, Adria (Frontiers in Immunology, 2025)
The Cre-Lox system is essential in biomedical research for precise gene deletion in specific cell types, crucial for understanding genetic roles in disease. Although generally considered non-detrimental, Cre recombinase expression has been associated with potential adverse effects, including Cre toxicity, ectopic expression, and disruption of endogenous genes. We investigated the role of macrophage nucleotide-binding oligomerization domain (Nod1) in obesity-associated diabetes using myeloid-specific Nod1-knockout mice (Nod1 floxed crossed with Lyz2Cre). Our study examined Lyz2Cre as well as floxed control mice separately, unlike most research. Results indicated that Lyz2Cre expression alone impacts glucose metabolism, challenging the notion that Cre expression is harmless. This finding highlights the critical importance of including Cre-only controls in studies using floxed alleles to generate conditional knockout mouse models in order to ensure robust and accurate conclusions in molecular research.